Autenticação de Ginseng brasileiro utilizando a técnica de High Resolution Melting (HRM) - Almeida, Francine Alves Nogueira de (2018)
As the herbal industry grows, the authenticity of its products is a matter of consumer safety and cannot be neglected. Brazilian Ginseng, for example, refers to two distinct species, Pfaffia glomerata and Hebanthe eriantha. Despite the similarity between these two species, which hinders morphological identification, they have different chemical and pharmacological properties. In this project we proposed a High Resolution Melting technique (HRM) as a tool to discriminate and identify P. glomerata and H. eriantha species using a matK and rbcL gene region. For this purpose, six reference samples were obtained, three of each of the aforementioned species, and 60 (sixty) commercial samples, sold as Brazilian Ginseng, through physical or online purchase. The DNA is extracted by the CTAB method and kit. The primer designed were tested through amplification by conventional PCR and confirmed in polyacrylamide gel before standardization of the PCR amplificationHRM and finally the results were compared to sequencing. Three primers were developed for the matK gene, two for the HRM-matKD and HRM-matK, and one for the rbcL gene , HRM-rbcL . During the standardization, the influence of the annealing temperature and the concentration of the primer on the race result was noticed, however, the extraction method did not change the results. The analysis of HRM showed that the first HRM-matKD was the one that met the proposed objective presenting high sensitivity (92-93%) and specificity (100%) compared to the sequencing method. It was possible to validate the HRM technique using previously sequenced commercial samples, which allows us to state that the HRM technique can be used to discriminate H. eriantha and P. glomerata. HRM is a fast and low cost method, being a reliable tool for identification of Brazilian Ginseng species.